Enhancing the secondary-tertiary transition in chemistry through formative assessment and self-regulated learning environments : final report. - Lawrie, Gwen (Office for Learning and Teaching, 2015)
It is desirable to enhance student learning trajectories between their secondary and tertiary studies while simultaneously encouraging them to take responsibility for their learning early in their tertiary studies. Their preparedness for tertiary studies in their discipline can be measured using diagnostic tests and this enables standards-based benchmarking as students progress through their tertiary program. Concept inventories have been used extensively for this purpose. A more desirable goal, however, is to use the outcomes of diagnostic testing to provide students with opportunities to improve their learning through formative feedback and self-regulated learning activities. This project aimed to design and implement modular, formative learning objects, informed by the outcomes of concept inventories, to target key missing and mis-conceptions possessed by incoming students. Students were able to challenge and adjust their existing conceptions by engaging in these discrete active learning modules (hosted by existing technologies) which were administered either in class or online in large chemistry classes. This document is the final report from the project.